2022
DOI: 10.3389/fonc.2022.896246
|View full text |Cite
|
Sign up to set email alerts
|

Scalp-Sparing Radiation With Concurrent Temozolomide and Tumor Treating Fields (SPARE) for Patients With Newly Diagnosed Glioblastoma

Abstract: IntroductionStandard-of-care treatment for patients with newly diagnosed glioblastoma (GBM) after surgery or biopsy includes concurrent chemoradiation followed by maintenance temozolomide (TMZ) with tumor treating fields (TTFields). Preclinical studies suggest TTFields and radiotherapy work synergistically. We report the results of our trial evaluating the safety of TTFields used concurrently with chemoradiation.MethodsThis is a single-arm pilot study (clinicaltrials.gov Identifier: NCT03477110). Adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…It is attractive to speculate that these transcriptional effects could be exploited to design mechanism-based synergistic combinations. In this respect it is worthwhile underlining that among the genes that were found modulated by TTFields there are some involved in DNA repair and DNA damage response, supporting the rational to combine TTFields with drugs causing DNA damage or radiotherapy, and some recent preclinical and clinical evidences support this hypothesis [ 12 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 97%
“…It is attractive to speculate that these transcriptional effects could be exploited to design mechanism-based synergistic combinations. In this respect it is worthwhile underlining that among the genes that were found modulated by TTFields there are some involved in DNA repair and DNA damage response, supporting the rational to combine TTFields with drugs causing DNA damage or radiotherapy, and some recent preclinical and clinical evidences support this hypothesis [ 12 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 97%
“… 73 When TTFields were given concurrently with RT which was delivered through the TTFields arrays and with maintenance TMZ, the PFS of 9.3 months was illustrated. 72 It follows that the feasibility of TTFields both as maintenance therapy and alongside chemoradiotherapy is endorsed by prior clinical practice, and a more large‐scale clinical trial, EF‐32(NCT04471844), is underway.…”
Section: Clinical Studies Of Ttfields In Malignant Brain Tumorsmentioning
confidence: 99%
“…In addition, Stein et al [ 95 ] reported a case of thalamic GBM, IDH wild-type, showing a complete radiological response after chemoradiation with TMZ, proton boost therapy, and TMZ maintenance in combination with TTFields therapy. Recently, Miller et al [ 96 ] evaluated the skin toxicity of scalp-sparing chemoradiation plus TTFields followed by maintenance TMZ plus TTFields in 30 patients with ndGBMs, showing good tolerance of the new protocol with no need to remove electric arrays during the radiation process, as well as a higher PFS in these patients than in the historical controls.…”
Section: Clinical Studies Of Ttfields Treatment On Gbmsmentioning
confidence: 99%